Content Vol. 43 No. 3 (2022) - Coordinador Editorial (Revista Mexicana de Ingenieria Biomedica, 2023)
E-book edition of the volume 43, number 3, year 2022, of the Revista Mexicana de Ingeniería Biomédica. In this issue: Vaginal Electrical Impedance Detects the Fertile Window in Healthy Women: a Pilot Study Segmentation of OCT and OCT-A Images using Convolutional Neural Networks Electrical Impedance Tomography to Measure Spirometry Parameters in Chronic Obstructive Pulmonary Disease Patients Book Review: “Medicine-Based Informatics and Engineering” Lecture Notes in Bioengineering, Springer, 2022 Detection of People Positive to COVID-19 through ATR-FTIR Spectra Analysis of Saliva using Machine Learning